Lettering, Mackinnon Mackenzie and Co. building - Ghosh, Ayan (2023)
Mackinnon Mackenzie and Co. was formed by William Mackinnon (1823-93) and Robert Mackenzie (1810-53). In 1856, Mackinnon Mackenzie and Co. secured East India Company's mail contract between Kolkata and Rangoon and founded the Calcutta and Burmah Steam Navigation Company Ltd, the forerunner to the British India Steam Navigation Company.